Sewerage and sewage disposal - Robinson, Henry (E. & F.N. Spon., 1896)
This title provides a concise summary of data on water supply, sewerage, and sewage disposal, touching on river pollution and filtration of impure water; it summarises necessary requirements for the drainage of houses and the sewering of towns, and deals with calculations of flow in sewers and of discharges and velocities in oval and circular sewers.